2020
DOI: 10.1007/s12070-020-01971-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine Governance of Difficult Tracheostomy in Difficult Airway with Stridor and Respiratory Distress

Abstract: Difficult airway is a commonly encountered problem in the anesthesia practice, might needing otolaryngologist expert in creation of surgical airway. Supraglottic airways, surgical or needle cricothyrotomy, high frequency jet ventilation, cardiopulmonary bypass (Tunstall in Can J Anaesth 36:611-613, 1989) are initial rescue measures in such scenario. But in otolaryngology practice, patient presenting with stridor having difficult airway and difficult tracheostomy concurrently will definitely pose problems resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…7 However, cases of morbid obesity and a short neck make the landmark difficult; even with the proper positioning, it fails to elevate the larynx and expose the upper trachea. 8 While maximising neck extension might bring the trachea closer to the skin, it might also bring up major blood vessels from the upper superior mediastinum into the pretracheal region, putting them at risk for injury. 9 An adequate exposure of trachea is important before making the incision by retracting the thyroid isthmus superiorly if it is located above the 3rd tracheal ring and small incision or complete dissection of the isthmus is located between the 2nd and 3rd tracheal rings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, cases of morbid obesity and a short neck make the landmark difficult; even with the proper positioning, it fails to elevate the larynx and expose the upper trachea. 8 While maximising neck extension might bring the trachea closer to the skin, it might also bring up major blood vessels from the upper superior mediastinum into the pretracheal region, putting them at risk for injury. 9 An adequate exposure of trachea is important before making the incision by retracting the thyroid isthmus superiorly if it is located above the 3rd tracheal ring and small incision or complete dissection of the isthmus is located between the 2nd and 3rd tracheal rings.…”
Section: Discussionmentioning
confidence: 99%
“…11 Soni et al reported 3 cases of difficult tracheostomies, one of which was short neck; with proper planning and imaging prior to the operation, the tracheostomy was successfully completed without complications. 8 Ultrasound neck before operation and using the combination of an ultrasound and a fibre optic video bronchoscope may improve the outcomes of percutaneous tracheotomy procedures in short-neck patients. 12 There have been a few case reports of early or late tracheostomy tube usage complications involving bleeding from the tracheoinnominate artery fistula, with the earliest date of presentation on 11th day after the operation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 High frequency jet ventilation, surgical or needle cricothyrotomy, supraglottic airways, and cardiopulmonary bypass are the initial rescue measures in difficult airway conditions. 10 Emergency cricothyrotomy is the final step in the “Can't intubate, can't oxygenate” (CICO) algorithm and is performed to prevent the patient's death. Complication rates vary by study, depending on the level of training, clinical scenario, or location of the procedure, and can range from 0 to 54%.…”
Section: Introductionmentioning
confidence: 99%